Historical blocking: CN 2022-11-12 to 2022-11-13 (China) - Voidly (2022)
CRITICAL severity censorship detected in China. Confidence: 98%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2022-0349
Keywords: censorship; CN; censorship; critical